Alterations in serotype-specific B cell responses to the 13-valent pneumococcal conjugate vaccine in aging HIV-infected adults - Ohtola, Jennifer A.; Khaskhely, Noor M.; Saul-Mcbeth, Jessica L.; Iyer, Anita S.; Leggat, David J.; Khuder, Sadik A.; Westerink, M.A. Julie (Vaccine, 2016)
Advanced age and human immunodeficiency virus (HIV) infection are associated with increased pneumococcal disease risk. The impact of these factors on cellular responses to vaccination is unknown. HIV-infected (HIV+) individuals 50–65 years old with CD4+ Tcells/μl (CD4) >200 on antiretroviral therapy (ART) ≥1 year received either the 13-valent pneumococcal conjugate vaccine followed by the 23-valent pneumococcal polysaccharide vaccine (PCV/PPV) or PPV only. HIV-uninfected (HIV−) controls received PCV/PPV. Phenotype distribution and surface expression of complement receptor CD21 and tumor necrosis factor superfamily receptors (TNFRs) were compared on serotype-specific B cells postvaccination. Postvaccination serotype-specific B cell percentages were significantly lower in HIV+ PCV/PPV compared to PPV groups, but similar between HIV+ or HIV− PCV/PPV groups. Transmembrane activator and calcium-modulating cyclophilin ligand interactor (TACI)+ serotype-specific B cell percentages were significantly decreased in HIV+ PCV/PPV compared to PPV groups. CD21+ serotype-specific B cells were significantly higher in HIV− compared to HIV+ PCV/PPV groups. An initial dose of PCV reduced the frequency, but not phenotype distribution, of serotype-specific B cells and also lowered TACI expression in aging HIV+ subjects postvaccination with PPV. These findings suggest that PCV does not enhance cellular responses to revaccination with PPV.